ETNOGRAFI DAN GENRE SASTRA REALISME SOSIALIS - Setyobudi, Imam (Institut Seni Indoensia Surakarta, 2009)
The ethnography writing was completely based on field (empiric) data. Anthropologist always holds on the present events. This article constitutes a beginning effort to design ethnography writing method using one genre or style in literature. Formerly, ethnography held on bourgeois realism. The writer changes realism in ethnography which doesnâ€™t seem potential and objective with militant social realism literature. The writer labels it â€œliberation ethnographyÂ â€œ. This article just takes a genre spirit of realism-socialist literature as â€œcontrasting literatureâ€ to become â€œliberation ethnographyâ€ or â€œethnography as a liberation movementâ€. The birth of anthropology with ethnography as its textual product represents the son of imperialist and colonialist. Along with the collapse of imperialist and colonialist, the awakening of ex-colonies to become new countries, entering post colonial era and global culture, the disorder of culture, the appearance of sub culture and counter culture, the foundation of anthropology becomes porous. The purpose of ethnography writing needs to be reviewed because there is an interest to write ethnography as a politi cal practice.Â Key words: Ethnography, Social Realism Literary, Liberation Ethnography